UJI EFEKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN GELUGUR (Garcinia atroviridis Griff ex. T Anderson)TERHADAP TIKUS JANTAN PUTIH (Rattus norvegicus) DENGAN LOPERAMIDE SEBAGAI PEMBANDING - Pintata Sembiring (Jurnal Penelitian Farmasi & Herbal, 2021)
Gelugur leaf (Garcinia atroviridis Griff ex T. Anderson) is a kind of nadir is believed to origanate from the wild forest of Peninsular Malaysia. Gelugur leaves have antidiarrheal compounds in the shapes of tannins and flavonoids to reduce diarrhea. The purpose of this study was to find out the antidiarrheal activity of the ethanolic extract of gelugur leaf in white male rats. The antidiarrheal effect was tested on 15 white male rats with 5 treatment groups, namely, a negative control group of 1% CMC Na, a positive control group of loperamidee hcl, and a treatment group of ethanol extract of gelugur leaves at a dose of 150 miligrams/kgBW, a dose of 300 miligrams/kgBW, and 600 miligrams/kg body weight. Each group was given oral treatment and observations were made on the onset of diarrhea, frequency of diarrhea, and stool consistency. Tests were carried out using an experimental method. The ethanol extract of gelugur leaves was made by maceration method using 96% ethanol. The results of the study on the onset of diarrhea were EEDG 600 miligrams/kgBB (60 minutes), a good decrease in diarrhea frequency was indicated by EEDG 600 miligrams/kgBB (4 times), a good decrease in stool weight was shown by EEDG 600 miligrams/ kgBB (0,7757 grams), good consistency was also shown in the EEDG 600 miligrams/kgBB (soft stools. The data were statistically analyzed using One Way Anova. The results of data analysis from the three EEDG groups affected the decrease in diarrhea because the sig value <0.05 Based on One Way Anova analysis, the five most effective treatments were loperamidee, 600 miligrams/kgBB, EEDG at 300 miligrams/kgBB, EEDG at 150 miligrams/kgBB, and CMC Na 1%. The conclusion in this study is that EEDG 600 miligrams/kgBB has antidiarrheal activity induced by oleum recini when compared with EEDG concentrations of 150 miligrams/kgBB and 300 miligrams/kgBB.